Achieving social development in Africa through Eafricamuamalat - Wudil, Adamu Ahmed; Md Saad, Norma; Lacheheb, Zakaria; Rislanudeen, Muhammad (Leadership Academy of Social Science, 2024)
This paper looks at how Islamic finance-based financial technology (IFT) solutions like eAfricaMuamalat can help to foster social development on a continent where the needs are great like Africa. It examines how eAfricaMuamalat can face up challenges such as poverty, lack of education and medical supplies as well as business operation through sustainable finance models. This paper takes a comprehensive approach including literature reviews and strategy papers. It conducts systematic analysis to confirm the compatibility of eAfricaMuamalat within Maqasid al-Shari’ah theory, integrating with a range of sustainable financing models that creates an ecosystem for social and economic development. Crowdfunding, impact investment, peer-to-peer lending, zakat, waqf and sadaqa all exist within eAfricaMuamalat. It is a comprehensive tool for investment, bond communities and fill gaps in inclusive finance. Simultaneously, presenting opportunities for change and charity work as well as the integration of resources within African countries. This paper also contributes to existing literature by introducing a new manner to incorporate Islamic financial principles into cutting-edge innovative financing models. It brings to light the potential of platforms such as eAfricaMuamalat in transforming the social dynamics of communities confronting outstanding problems of social development.